The perception of al-'Adl in critical thinking: A comparative study of Muslim engineering undergraduates in Malaysian universities - Al-Amin Endut, M.N. (Universiti Putra Malaysia, 2014)
The element of justice or al-'adl in the context of Islamic critical thinking deals with the concept of justice as informing the thought process that critically rationalises the truth in a fair and objective manner with no irrelevant interference that can jeopardise a sound judgment. This Islamic axiological element is vital in technological decision-making as it addresses the issues of religious values and ethics that are primarily set to fulfill the purpose of human life on earth. The main objective of this study is to reveal the distinguished element of al-'adl in Islamic critical thinking and determine the significance of the perception to Muslim engineering students from different Malaysian universities. This comparative study looks into the factors that lead to a better comprehension among the undergraduates of the concept of al-'adl in critical thinking. The study employed the survey method and Analysis of Variance (ANOVA) technique involving 549 Muslim engineering undergraduates from six Malaysian universities. The results generally indicate that undergraduates who have been exposed to the Islamic perspective of critical thinking possess a significantly clearer idea of the concept of al-'adl. The study also suggests that faculties of engineering in Malaysian universities should reconsider the current concept of critical thinking and embed in it elements of Islamic critical thinking. Â© Universiti Putra Malaysia Press.